Analisis Pengadaan Barang Dagang Dalam Meningkatkan Pelayanan Terhadap Anggota Koperasi - Pebriani, Agista; Lulus Setiawan, Wawan; Rainy Firohmatillah, Agrivinie (Coopetition : Jurnal Ilmiah Manajemen, 2025)
Koperasi Keluarga Besar RS Al Islam “Amanah” is a primary cooperative whose members are all the employees who work under the West Java RSI KSWI Foundation. There are three business units namely The Savings And Loans Unit, The Mart Unit, And The Canteen And Catering Unit. However in running its business the cooperative experienced several problems, such as decreasing member satisfaction in terms of service in unit mart. The results of this research shows the merchandising received a final score of 2,311 with the criteria “not good”, it can be seen that merchandising at KKB “Amanah” mart unit has not been able to fulfill member’s wants and needs. There are five assessments of service indicators that are still in a "not good" score 2554. Then the effort for increasing services are completing the merchandise, solving the problem of accuracy of stock items, improving the employee's skill, and improving the elements of services in the KKB “Amanah” mart unit.